The impact of self-isolation on the socio-psychological state of a person: research results - R. M. Ahmadinurov; S. N. Ispulova; E. V. Oleynik; I. V. Bochkarev; E. D. Vinogradova (Вестник университета)
Based on the analysis of the results of the survey conducted by the authors through a service such as Google Forms, some aspects of the impact of the COVID-19 coronavirus pandemic on the socio-psychological state of a person are considered. The sample of respondents can be described as spontaneous. The age of respondents in the range from 14 to 71 years, these are residents of different states, localities, differing in the nature of leading activities and social status. However, the results of the study demonstrate that place, age, status and other characteristics are not crucial in terms of socio-psychological well-being during the pandemic. Among the main problems faced by the population in the conditions of the pandemic are limited contacts and movement, difficulties with the organization of school-age children’s studies, loss of work and reduced income, fear for their health and the health of loved ones.